People, Objects and Actions: A Multimodal Discourse Analysis of the Ideational Metafunction in Internet Memes - Ángel Jiménez Lina Paola (Eximia, 2024)
Memes are complex forms of communication that utilize images and text to convey various ideas, beliefs, emotions, and behaviors. This study seeks to identify and analyze the elements within memes, including the participants and actions depicted in the visual and textual components. To achieve this, a selection of sixty-five memes was subjected to in-depth analysis using Multimodal Discourse Analysis, Halliday’s Transitivity System, and Kress and Van Leeuwen’s image analysis theory. As a result of this analysis, four categories of textual participants and four categories of visual participants were identified. Also, actions were classified according to Halliday’s Transitivity system.